Posthatching water and feed deprivation affect the gastrointestinal tract and intestinal mucosa development of broiler chicks - Maiorka, A.; Santin, E.; Dahlke, F.; Boleli, I. C.; Furlan, R. L.; Macari, Marcos [UNESP] (Poultry Science Assoc Inc, 2003)
We studied the effect of feed and water deprivation on gastrointestinal tract and intestinal mucosa development of chicks at 24, 48, and 72 h posthatching. The treatments were water and feed ad libitum, water ad libitum and no feed, no water but feed ad libitum, and no water and no feed. The relative weight of the yolk sac was not influenced by the treatments. However, at 48 and 72 h posthatching, the relative weight of the liver increased, and the gizzard + proventriculus weight decreased in birds receiving feed ad libitum. An increase in jejunum and ileum relative weights and lengths was observed when the birds were supplied with feed and water. The lack of water produced the same effect as the lack of feed, both causing a higher number of villi per area with reduction in villus size, when compared with feed and water ad libitum treatments. The results of this study revealed that feed and water are able to affect intestinal villus development after hatching, indicating that both feed and water must be supplied to the chicks immediately after hatching.
Keywords: chick; feed; gastrointestinal tract; mucosa development; water